Adenosine A₃ Receptor Mediates ERK1/2- and JNK-Dependent TNF-α Production in Toxoplasma gondii-Infected HTR8/SVneo Human Extravillous Trophoblast Cells - Ye, Wei; Sun, Jinhui; Li, Chunchao; Fan, Xuanyan; Gong, Fan; Huang, Xinqia; Deng, Mingzhu; Chu, Jia-Qi (Korean journal of parasitology, 2020)
Toxoplasma gondii is an intracellular parasite that causes severe disease when the infection occurs during pregnancy. Adenosine is a purine nucleoside involved in numerous physiological processes; however, the role of adenosine receptors in T. gondii-induced trophoblast cell function has not been investigated until now. The goal of the present study was to evaluate the intracellular signaling pathways regulated by adenosine receptors using a HTR-8/SVneo trophoblast cell model of T. gondii infection. HTR8/SVneo human extravillous trophoblast cells were infected with or without T. gondii and then evaluated for cell morphology, intracellular proliferation of the parasite, adenosine receptor expression, TNF-α production and mitogen-activated protein (MAP) kinase signaling pathways triggered by adenosine A3 receptor (A3AR). HTR8/SVneo cells infected with T. gondii exhibited an altered cytoskeletal changes, an increased infection rate and reduced viability in an infection time-dependent manner. T. gondii significantly promoted increased TNF-α production, A3AR protein levels and p38, ERK1/2 and JNK phosphorylation compared to those observed in uninfected control cells. Moreover, the inhibition of A3AR by A3AR siRNA transfection apparently suppressed the T. gondii infection-mediated upregulation of TNF-α, A3AR production and MAPK activation. In addition, T. gondii-promoted TNF-α secretion was dramatically attenuated by pretreatment with PD098059 or SP600125. These results indicate that A3AR-mediated activation of ERK1/2 and JNK positively regulates TNF-α secretion in T. gondii-infected HTR8/SVneo cells.